HLA and AB0 Polymorphisms May Influence SARS-CoV-2 Infection and COVID-19 Severity. Issue 1 (January 2021) - Amoroso, Antonio; Magistroni, Paola; Vespasiano, Francesca; Bella, Antonino; Bellino, Stefania; Puoti, Francesca; Alizzi, Silvia; Vaisitti, Tiziana; Boros, Stefano; Grossi, Paolo Antonio; Trapani, Silvia; Lombardini, Letizia; et al.
Abstract : Background: SARS-CoV-2 infection is heterogeneous in clinical presentation and disease evolution. To investigate whether immune response to the virus can be influenced by genetic factors, we compared HLA and AB0 frequencies in organ transplant recipients and waitlisted patients according to presence or absence of SARS-CoV-2 infection. Methods: A retrospective analysis was performed on an Italian cohort composed by transplanted and waitlisted patients in a January 2002 to March 2020 time frame. Data from this cohort were merged with the Italian registry of COVID + subjects, evaluating infection status of transplanted and waitlisted patients. A total of 56 304 cases were studied with the aim of comparing HLA and AB0 frequencies according to the presence (n = 265, COVID + ) or absence (n = 56 039, COVID – ) of SARS-CoV-2 infection. Results: The cumulative incidence rate of COVID-19 was 0.112% in the Italian population and 0.462% in waitlisted/transplanted patients (OR = 4.2; 95% CI, 3.7-4.7; P < 0.0001). HLA-DRB1*08 was more frequent in COVID + (9.7% and 5.2%: OR = 1.9, 95% CI, 1.2-3.1; P = 0.003; P c = 0.036). In COVID + patients, HLA-DRB1*08 was correlated to mortality (6.9% in living versus 17.5% in deceased: OR = 2.9, 95% CI, 1.15-7.21; P = 0.023). Peptide binding prediction analyses showed that these DRB1*08 alleles were unable to bind any of the viral peptides with high affinity. Finally, blood group A was more frequent in COVID + (45.5%) than COVID – patients (39.0%; OR = 1.3; 95% CI, 1.02-1.66; P = 0.03). Conclusions: Although preliminary, these results suggest that HLA antigens may influence SARS-CoV-2 infection and clinical evolution of COVID-19 and confirm that blood group A individuals are at greater risk of infection, providing clues on the spread of the disease and indications about infection prognosis and vaccination strategies.